Manuscripts and rare books of Alisher Navoi in Almaty Library Founds - G. Kambarbekova; G. Abikova (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2022)
One of the most important topics is studying the works of the poet Mir Alisher Navoi common to the entire Turkic world and presenting them to today's Kazakhstan readers. The purpose of the article is to acquaint with the manuscripts and rare editions of Alisher Navoi, which have not been studied and noticed by scientists for many years. Alisher Navoi is a bilingual poet and left behind many works. To date, we know about thirty of his works. Kazakhstan readers are familiar with some of these works, and they are still not familiar with some of them. We note the need to study the works of the poet based on the original text and translate them directly from the original into the Kazakh language. Alisher Navoi became very popular during his lifetime. They passed his works from hand to hand, often copied, it widely distributed in many lists of his works throughout the country. For this reason, the poet's manuscripts can be found in the most famous libraries in the world. Among these libraries is the National Library of the Republic of Kazakhstan and the Central Scientific Library. The article systematizes the works of Alisher Navoi, which are stored in the above-named libraries. Also, a source study and linguistic analysis of his works were carried out. Each manuscript and rare edition of Alisher Navoi has its own history. Therefore, issues of conservation, letters, covers, scribes, customers, and owners of the poet's manuscripts will be considered. Key words: manuscript, lithography, Chagatai literature, Alisher Navoi, Khamsa, Mahbub al-kulub, National Library, Central Scientific Library.